F. Brantley Scott: a visionary in the world of urology. Issue 3 (May 2018) - Carson, Culley C
Abstract : F. Brantley Scott was a urologist, surgeon, neuroscientist and inventor, but most importantly a visionary in modern medicine. Culley Carson looks back at the achievements of a true renaissance man who left an enduring stamp on the field of urology.